Análisis de contenido de la plataforma digital del Diario los Andes referente al Covid 19 en el Ecuador, período enero 2020 – junio 2020 - Daniela Fernanda, Tenemaza Illicachi (2021)
Abstract This research work, named “Analysis of Digital Platform Content from the newspaper Los Andes concerning to Covid 19 in Ecuador, during the period January 2020 - June 2020”, was developed with the purpose of determining whether the medium published regular information about the mentioned topic on its digital boards. In addition, it pretends to determine if the publications on the newspaper's website comply with the quality and characteristics of a digital medium to inform the community about the pandemic in a proper manner, for that reason a content analysis matrix was developed, which took into account the main elements such as: publication date, news headline, URL, audience, resources, journalistic genre, source, verbs, tone and visits of the information collected during the period January-June 2020 and there where obtained a total of 36 analysis items. Besides, to support this investigation an interview analysis sheet was prepared, which were conducted with experts on the subject of journalism and digital communication, who evidenced and are witnesses to this health emergency, professionals from the communication from Guayaquil, Quito and from the Regional Newspaper Los Andes de Riobamba. In this research, it was evidenced that the publications on the newspaper's website partially comply with the characteristics of digital content such as multimedia, opting for images, the interaction that is allowed exclusively for subscribers and there is no hypertextuality. By not fully complying with these properties, the inadequate possibility of generating a correct edition of content on the website of this media is evidenced. To accomplish this investigative work, a basic manual for the writing of digital content publication was developed for the regional newspaper Los Andes from Riobamba, which is centered on the writing rules and journalistic style, which will serve as support to the journalists of the medium to develop their publications on the website and digital platforms, providing suggestions for reporting and proper use of digital tools during communication in times of health crisis. Key Words: Content analysis, Digital Journalism, COVID 19, Manual for Digital Journalism, Los Andes Regional Newspaper, Riobamba. Reviewed: Lic. Jesús Guevara Sánchez ENGLISH TEACHER CC: 0603947441